2000
DOI: 10.1302/0301-620x.82b1.0820033
|View full text |Cite
|
Sign up to set email alerts
|

Proximal entry for intramedullary nailing of the tibia

Abstract: T he risk of articular penetration during tibial nailing is well known, but the incidence of unrecognised damage to joint cartilage has not been described. We have identified this complication in the treatment of tibial fractures, described the anatomical structures at risk and examined the most appropriate site of entry for tibial nailing in relation to the shape of the bone, the design of the nail and the surgical approach.We studied the relationship between the intra-articular structures of the knee and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 9 publications
1
39
0
1
Order By: Relevance
“…The ideal entry point for tibial nailing had been reported by several authors [2][3][4][5][6]. Samuelson MA et al [2] reported to be at the medial aspect of the tibial tubercle in coronal plane.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The ideal entry point for tibial nailing had been reported by several authors [2][3][4][5][6]. Samuelson MA et al [2] reported to be at the medial aspect of the tibial tubercle in coronal plane.…”
Section: Discussionmentioning
confidence: 94%
“…O Lembcke et al revealed that too lateral entry point caused a varus deformity and too medial entry point created a valgus deformity [3]. Hernigou P, Cohen D [4] revealed that 2.5mm (+/-1.8mm) lateral to the centre of the tibial tubercle is an ideal entry point. Too distal entry point leads to proximal posterior cortex breakage.…”
Section: Introductionmentioning
confidence: 99%
“…The causes of knee pain are multifactorial and protruded nail alone cannot be blamed. Many intra-articular and extra articular structures are believed to be responsible for knee pain after tibia nailing [22][23][24] .…”
Section: Discussion:-mentioning
confidence: 99%
“…Hence they recommend entry point anterior to the transverse ligament and anterior horn of each meniscus 23 . McConnell et al,based on their study on cadaveric knees recommended entry point medial to the lateral tibial spine and anterior to articular margin to avoid articular cartilage damage 24 .…”
Section: Discussion:-mentioning
confidence: 99%
“…The proximity of IM tibial nail placement to articular tissues may adversely influence knee extensor mechanism function [11]. The patellar ligament transfers the locomotion and dynamic knee joint control stabilizing forces of the quadriceps femoris muscle group to the lower leg during function.…”
Section: Introductionmentioning
confidence: 99%